Diagnostic performance of alpha-fetoprotein, YKL40 and GP73 in hepatocellular carcinoma Egyptian patients - Ali, Fahmy T.; Elhady, Mostafa M.; Fawzy, Amal M.; Abdelgawad, Ahmed A. (International Journal of Research in Medical Sciences, 2016)
Background: Hepatocellular carcinoma (HCC) is a primary malignancy of the liver. It is responsible for a large proportion of cancer deaths worldwide. Diagnosis of HCC often requires more sophisticated modalities and represents a challenge for physician. Methods: This study aimed to compare the diagnostic performance of AFP, YKL40 and GP73 in patients' serum with hepatocellular carcinoma (HCC) in high-risk population in an attempt to justify the new, sensitive, specific and rapid measure for the diagnosis and detection of HCC. Serum YKL40, GP73 and alpha-fetoprotein (AFP) were compared in a total of 60 human subjects in this study, including 20 healthy adults, and 40 patients with HCC, The main outcome measures were the specificity and sensitivity of YKL40 and GP73 in patients at risk for the development of HCC. Results: Using 4.4 relative units as a cut-off value, the sensitivity and specificity of serum GP73 for HCC were 85% and 90% compared with 77% and 60% for YKL40 using 21.06 ng/ml as a cut-off value. On the same context, the sensitivity and specificity of serum AFP at 8.5ng/ml cut-off were 82% and 95%. While that for the AFP and GP73 combined detection was up to 92% and 96%, justifying that the combined detection could prevent the false negative diagnosis by any marker alone and significantly improve the detection rate of HCC. Conclusions: The current evidence indicates that serum GP73 has HCC diagnostic efficacy inferior to that of AFP and YKL40 and the clinical implementation of serum GP73 measurement as a standard test for HCC is recommended alone or in combination with AFP.